Cold-induced metabolic adaptations in the large yellow croaker Larimichthys crocea - Yang Gao; Huirong Lv; Chengzhang Huang; Xiaoyu Qu; Zhangjie Chu; Weiye Li; Xiaolong Yin; Jungyeol Park; Dejun Feng; Junwook Hur (Aquaculture Reports)
Large yellow croaker is one of the most important marine aquaculture species in China. However, due to its intolerance to low temperatures, overwintering often results in deaths, causing significant economic losses. In a controlled laboratory experiment, we assessed the impact of temperature and water current on the overwintering behavior of large yellow croaker using a swimming flume. The experiment was divided into two temperature conditions (8°C and 20°C) and four flow rates (15 cm/s, 20 cm/s, 25 cm/s, and 30 cm/s). We measured sustained swimming time, tail beat frequency, opercular respiratory rate, and conducted transcriptomic and metabolomic analyses. Our findings indicate that lower temperatures and higher flow rates reduce sustained swimming time. Flow rate had a more significant impact on tail beat frequency than temperature, whereas respiratory rate was more affected by temperature than flow rate. Omics data revealed that the ABC transporter, glycolysis and oxidative phosphorylation pathways were downregulated, whereas the citrate cycle pathway was upregulated, suggesting a metabolic adjustment to optimize ATP production and cellular transport mechanisms for efficient energy utilization and metabolic homeostasis. This study concludes that colder temperatures compromise metabolic efficiency and increase energetic demands, leading to fatigue and diminished endurance. Large yellow croakers adapt to cold temperatures by relying more on the citrate cycle and less on glycolysis and oxidative phosphorylation for energy. These findings offer a scientific basis for developing more resilient aquaculture systems that can better support the overwintering survival and overall health of large yellow croaker, thereby contributing to more sustainable and productive aquaculture operations.